2021
DOI: 10.2147/rmhp.s316361
|View full text |Cite
|
Sign up to set email alerts
|

Using the Apriori Algorithm to Explore Caregivers’ Depression by the Combination of the Patients with Dementia and Their Caregivers

Abstract: Purpose The purpose of this study was to identify the caring scenarios that result in severe depression in caregivers caring for dementia patients. Patients and Methods A cross-sectional study with 1111 dementia patients and their caregivers in Taiwan from October 2015 to January 2020 was conducted. Gender, age, type of dementia, clinical dementia rating, walking ability, mood symptoms, behavioral symptoms, and psychological symptoms were the variables from the dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(69 reference statements)
2
8
0
Order By: Relevance
“…Previous studies associated caregiver depression with being younger, having White or Hispanic ethnicity (compared to black ethnicity), having a lower educational level, and caring for a patient with ADL dependence[ 40 , 41 ], and behavioral disturbances[ 41 , 42 ]. There is significant evidence that BPSD influence depression in caregivers and may be more influential than the severity of cognitive deficits seen or perceived in the patient[ 43 , 44 ].…”
Section: Factors Associated With Caregiver Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies associated caregiver depression with being younger, having White or Hispanic ethnicity (compared to black ethnicity), having a lower educational level, and caring for a patient with ADL dependence[ 40 , 41 ], and behavioral disturbances[ 41 , 42 ]. There is significant evidence that BPSD influence depression in caregivers and may be more influential than the severity of cognitive deficits seen or perceived in the patient[ 43 , 44 ].…”
Section: Factors Associated With Caregiver Depressionmentioning
confidence: 99%
“…For dementia caregivers, factors associated with depression risk include having a low income, spending more hours caregiving (40 to 79 h/wk compared to less than 40 h/wk)[ 40 ], being female[ 41 ], having a spousal relationship[ 40 , 57 ], living with the patient[ 41 , 44 , 58 ], having poorer health status[ 44 , 58 ], and having a higher caregiver distress sensation[ 44 , 58 , 59 ]. It has been reported that approximately 80% of caregivers have some form of sleep disturbance.…”
Section: Factors Associated With Caregiver Depressionmentioning
confidence: 99%
“…Most of the studies explore the relationships between the dementia patient and caregiver sociodemographics, patient illness characteristics, and caregiver burden and depressive and anxiety symptoms. Illness severity and presence of behavioural and psychological symptoms of dementia (BPSD) are known predictors for caregiver burden and depressive and anxiety symptoms [25,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. PwD and the caregivers' sociodemographic background have also been studied in Malaysia and in other countries [18,44,49].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to identify which attributes from patients and/or caregivers could result in different usages of the LTC services. The Apriori algorithm has been proven to be very effective in identifying statistical correlations from a multidimensional viewpoint in dementia-related areas by setting up support, confidence, and lift (Jhang et al, 2019 , 2020 ; Chang et al, 2021 ). Thus, the Apriori algorithm was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the Apriori algorithm was used in this study. The definitions and formulas of support, confidence, and lift are given below (Chang et al, 2021 ; Jhang et al, 2021 ). The support of an association rule A ⇒ B is defined by calculating the percentage of transactions containing both A and B in the database depicted in Equation (1):…”
Section: Methodsmentioning
confidence: 99%